Anticancer potential of Phoenix dactylifera L. seed extract in human cancer cells and pro-apoptotic effects mediated through caspase-3 dependent pathway in human breast cancer MDA-MB-231 cells: an in vitro and in silico investigation - Mohsin Ali Khan; Romila Singh; Sahabjada Siddiqui; Imran Ahmad; Rumana Ahmad; Shivbrat Upadhyay; Md. Abul Barkat; Ahmed Mahmoud Abdelhaleem Ali; Qamar Zia; Aditi Srivastava; Anchal Trivedi; Ishrat Husain; et al. (BMC, 2022)
Abstract Background Phoenix dactylifera L. has a diverse set of pharmacological properties due to its distinct phytochemical profile. The purpose of this study was to investigate the anticancer potential of Phoenix dactylifera seed extract (PDSE) in human breast cancer MDA-MB-231 and MCF-7 cells, as well as liver cancer HepG2 cells, and to investigate the anticancer efficacy in triple-negative MDA-MB-231 cells, followed by in silico validation of the molecular interaction between active components of PDSE and caspase-3, an apoptosis executioner protein . Methods In this study, human cancer cell lines were cultured and subsequently treated with 10 to 100 μg/mL of PDSE. MTT test was performed to determine the cell viability, MMP was measured using fluorescent probe JC-1, nuclear condensation was determined by Hoechst 33258 dye, Annexin V-FITC & PI staining and cell cycle analysis were evaluated through flow cytometer, and apoptotic markers were detected using western blotting. The bioactive agents in PDSE were identified using high-performance liquid chromatography (HPLC) analysis. The binding affinity was validated using molecular docking tools AutoDock Vina and iGEMDOCK v2.1. Results Cell viability data indicated that PDSE inhibited cell proliferation in both breast cancer cells and liver cancer cells. MDA-MB-231 cells showed maximum growth inhibition with an IC50 value of 85.86 μg/mL for PDSE. However, PDSE did not show any significant toxicity against the normal Vero cell line. PDSE induced MMP loss and formation of apoptotic bodies, enhanced late apoptosis at high doses and arrested cells in the S phase of cell cycle. PDSE activated the enzymatic activity of cleaved caspase-3 and caused the cleavage of poly-ADB ribose polymerase (PARP) protein. PDSE upregulated pro-apoptotic Bax protein markedly but  no significant effect on tumor suppressor protein p53, while it downregulated the anti-apoptotic Bcl-2 protein expression. HPLC analysis showed the presence of rutin and quercetin bioactive flavonols in ethanolic extract of PDS. Interestingly, both active components revealed a strong binding interaction with amino acid residues of caspase-3 (PDB ID: 2XYP; Hetero 4-mer - A2B2) protein. Conclusion PDS could serve as a potential medicinal source for apoptotic cell death in human breast cancer cells and, thus, could be used as a promising and crucial candidate in anticancer drug development. This study warrants further in vivo research, followed by clinical investigation.